Efektivitas Konseling di Berbagai Bidang: Review Literatur Sistematis - Alfareza Wildan Pratama; Erdilla Apriliani Ananda; Tengku Iqbal Al Kabir; Regina Viola Lenity (Jurnal Psikologi, 2026)
This study examines the effectiveness of counseling interventions across educational, clinical, and social contexts through a Systematic Literature Review (SLR). The research aims to identify and classify counseling approaches and service formats, compare the effectiveness of Cognitive Behavioral Therapy (CBT) and Solution Focused Brief Therapy (SFBT), and analyze recent trends and innovations in counseling services. The study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to ensure a systematic and transparent review process. Literature was collected from Google Scholar, Garuda, DOAJ, and Scopus databases, focusing on articles published between 2021 and 2026. A total of 120 articles were initially identified, and after screening, eligibility assessment, and duplicate removal, 40 articles met the inclusion criteria and were analyzed using thematic synthesis. The findings indicate that counseling interventions are generally effective in improving psychological well-being, academic resilience, emotional regulation, and social functioning. Individual counseling was found to be more effective for trauma, stress, and emotional problems, while group counseling was more beneficial for social interaction, peer support, and self-compassion. CBT demonstrated strong effectiveness in producing long-term behavioral change, whereas SFBT was more suitable for short-term, solution-oriented interventions. In addition, digital and spiritually integrated counseling approaches showed increasing relevance and accessibility in modern counseling practice. Overall, counseling effectiveness depends on the compatibility between intervention approaches, service formats, and client needs. These findings provide guidance for counselors in selecting appropriate interventions and emphasize the need for experimental and comparative studies involving broader populations, diverse cultural contexts, and longitudinal evaluation designs.